KUTTAB SEBAGAI PUSAT ILMU PENGETAHUAN PENDIDIKAN ISLAM - Emna Laisa (Rabbani: Jurnal Pendidikan Agama Islam, 2020)
ABSTRACTKuttab has a strategic role in shaping the youth of Islam in the classical era. It is not only excelled in the religious and moral aspects, but also plays a role in the increased intellectual and life skills. Kuttab development from the Prophet era until the Abbasid Daula characterized in each period, in terms of the development of course materials, teaching methods, to community participation. In the midst political conflict, the existence kuttab always in a dynamic conditions. This is evident shows since kuttab just a personal waqf institution to become a major educational institution who participated managed by the government. Kuttab not only sparkling in the golden age, but kuttab inspire the implementation of the Full Day School in Indonesian Islamic educational institutions. It lies the urgency of term al-muhafadzah ala al-qadim al-shalih wa al-akhdu bi al-jadid al-ashlah, that the classical Islamic education system is able to be a reference to answer the problems of education in the contemporary era. ABSTRAKKuttab memiliki peran strategis dalam upaya pembentukan generasi muda Islam di era klasik. Kuttab tidak hanya unggul dalam aspek keagamaan dan moral, namun juga berperan dalam peningkatan intelektualitas dan kecakapan hidup. Perkembangan kuttab dari masa Rasulullah hingga Daulah Abbasiyah memiliki ciri khas dalam setiap periodesasinya, baik ditinjau dari pengembangan materi pelajaran, metode pembelajaran, hingga peran serta masyarakat. Di tengah suasana konflik politik yang berkecamuk, eksistensi kuttab senantiasa berada dalam kondisi dinamis.Hal ini tampak sejak kuttab hanya berupa institusi wakaf pribadi hingga menjadi institusi pendidikan besar yang turut serta dikelola pemerintah. Kuttab tidak hanya bersinar di masa keemasannya, tetapi telah menginspirasi pemberlakuan Full Day School di lembaga pendidikan Islam, khususnya di Indonesia. Di sinilah letak urgensi al-muhafadzah ala al-qadim al-shalih wa al-akhdu bi al-jadid al-ashlah, bahwa sistem pendidikan Islam klasik mampu dijadikan rujukan untuk menjawab masalah pendidikan di era kekinian.